Efektivitas Panduan Berbasis Infografis Interaktif dalam Meningkatkan Pengetahuan tentang Diabetes Melitus - Ismail Ismail; Selfi Wulandari; Muhammad Basri; Ratnawati Ratnawati (Celebes Health Journal, 2025)
Background: Diabetes Mellitus remains a common health problem among adolescents, primarily due to their low knowledge of risk factors, symptoms, and prevention. This low level of health literacy demonstrates the need for engaging and easy-to-understand educational media. Objective: This study aims to assess the effectiveness of an interactive infographic-based guide in improving respondents' knowledge of Diabetes Mellitus. Methods: The study used a pre-experimental one-group pre-test and post-test design involving 15 adolescent respondents selected through purposive sampling. The intervention was carried out by providing an interactive infographic guide for three days, then the respondents' knowledge level was re-measured using a structured questionnaire. Results: The results showed a significant increase in knowledge, where the good knowledge category increased from 6.7% to 73.3%. The Shapiro–Wilk test showed that the data were normally distributed, so the analysis was continued using a paired t-test which produced a p-value of 0.000 Conclusions: The interactive infographic guide is effective in improving respondents' understanding of Diabetes Mellitus. This study shows that interactive visual media can be an engaging and relevant educational alternative to improve health literacy in adolescent